Anti-Vascular Endothelial Growth Factor Therapy as an Alternative or Adjunct to Pan-Retinal Photocoagulation in Treating Proliferative Diabetic Retinopathy: Meta-Analysis of Randomized Trials - Gao, Shuang; Lin, Zhongjing; Shen, Xi (Frontiers in Pharmacology, 2020)
Aim: To compare anti-vascular growth factor (anti-VEGF) pharmacotherapy with pan-retinal photocoagulation (PRP) for proliferative diabetic retinopathy (PDR). Method: PubMed, Embase, Medline, the ClinicalTrials.gov and the Cochrane Central Register of Controlled Trials were reviewed systemically. Randomized controlled trials (RCT) on anti-VEGF therapy versus PRP or anti-VEGF agent combined with PRP versus PRP for PDR are eligible to be included. Outcome measures were regression and recurrence of neovascularization, change in best corrected vision acuity, development of vitreous hemorrhage and need for vitrectomy. A meta-analysis was conducted using RevMan (Cochrane Collaboration, Oxford, United Kingdom). Results: Twelve RCTs with a total of 1026 eyes were identified. The meta-analysis results showed that regression of neovascularization didn’t vary significantly among different treatment regimens (P=0.06), whereas the recurrence of new vessels was significantly lower in PRP monotherapy (P < 0.00001). The best corrected visual acuity was significantly improved with anti-VEGF monotherapy or in the combined group than in the PRP groups (P＜0.00001, P=0.04, respectively). Odds ratio for post-treatment vitreous hemorrhage and vitrectomy rate between anti-VEGF therapy and PRP were 0.65 (95% confidence interval, 0.45-0.95; P=0.03), and 0.24 (95% confidence interval, 0.12-0.48; P<0.0001). Conclusion: Our meta-analysis indicates that anti-VEGF pharmacotherapy is associated with superior visual acuity outcomes and less PDR-related complications. However, there is insufficient evidence to suggest anti-VEGF therapy as an alternative to PRP.